PEMANFAATAN TAUTAN APLIKASI LINKTREE SEBAGAI MEDIA INFORMASI LAYANAN REKAM MEDIS DI PUSKESMAS AMBACANG PADANG - Hendra Nusa Putra; Ade Wisandra; Dwi Ayu Lathifah (Ensiklopedia of Journal, 2023)
The use of internet as an online communication medium that is widely used by the public, especially for health center information services, can be used as a media for promotion and information in providing health services. The obstacle faced thus far is the lack of information for patients regarding these services. This study aimed to provide an application design as a supporting facility for patients. The services provided are in the form of a linktree application accompanied by a barcode developed using the Unified Modeling Language (UML), namely, Use Cases, Activity Diagrams, and Flowcharts. In the application, there are required information items such as the Puskesmas Profile Blog, Puskesmas YouTube, Puskesmas Instagram, online registration via (WhatsApp), Puskesmas Maps, and virtual advice contacts. This research method involves research and development (R&D). The informants interviewed in this study included two medical record officers and three patients. The Linktree application at the Ambacang Health Center was tested to run well. This link tree application is efficient and has been used effectively. Responses from the officers and patients were positive. Researchers hope that this link tree application can be used for sustainability in health services.